Kontribusi Motivasi Belajar Dan Pemanfaatan Fasilitas Labor Terhadap Hasil Belajar Mata Pelajaran Melakukan Perawatan Komputer Siswa Kelas X Teknik Komputer Dan Jaringan Di SMK Negeri 8 Padang - Muhammad Iqbal; Zulkifli Naansah; Yusri Abdul Hamid (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research is purposed to reveal the contribution oflearning motivation and laboratory facilities of the subjectslearning outcomes Perform Computer Maintenance Class Xstudent of Computer Engineering and Networks SMK Negeri 8Padang. The research is a descriptive correlational . The researchpopulation numbered is 59 people and sample totaled 37 studentsof class X Computer Engineering and Networks SMK Negeri 8Padang Academic Year 2012/2013.Using Technique of randomsampling ( Simple random sampling ) . and Data collection usingquestionnaires and documentation . Data were analyzed usingPearson product moment correlation and multiple correlation foranalysis . The results of data analysis showed : ( 1 ) learningmotivation to contribute 25.16 % of the learning outcomes ofstudents of SMK Negeri 8 Padang Academic Year 2012/2013 ,(2) laboratory facilities accounted for 19.82 % of the learningoutcomes of students of SMK Negeri 8 Champaign AcademicYear 2012/2013 , (3) Learning Motivation and Labor facilitiestogether accounted for 27.84 % of the learning outcomes ofstudents of SMK Negeri 8 Padang Academic Year 2012/2013 . Soit can be concluded that the motivation to learn and laboratoryfacilities contribute to the learning outcomes , the higher thestudents' motivation in the learning process and the betterutilization of laboratory facilities , the learning outcomes will behigher.